Answer:
no its not
Step-by-step explanation:
what is 16/14 in mixed number
Answer:
1 2/14
Step-by-step explanation:
PLZ HELP ASAP ILL GIVE BRAINLEST PLZ
Answer:
the answer is yes
Step-by-step explanation:
k(3)=5(3)-3
k(3)=15-3
k(3)=12
12 is the answer
worth 10 points please help
If x = -2, which inequality is true?
Answer:
3 - x <10
Step-by-step explanation:
plug in -2 as x in each equation and see if its true
2(-2) + 6 < -1 -- false
2(-2) - 3 > 6 false
-5 + 3(-2) > 1 false
Due to erosion, a beach is
disappearing at a rate of -5 feet
per year. How long will it take for
the beach to lose 85 feet
Answer:
17 years
Step-by-step explanation:
do 85 divided by 5
Answer:
17 years
Step-by-step explanation:
-5 feet = 1 year
To do this you would do:
85 ÷ 5 = 17 years
Hope this helps!
165 =-3(-8v + 1) + 4v
Thank you
Answer:
v=6
Step-by-step explanation:
Does anyone know how to do this?? Help please!!!!
Answer:
When we have a rational function like:
[tex]r(x) = \frac{x + 1}{x^2 + 3}[/tex]
The domain will be the set of all real numbers, such that the denominator is different than zero.
So the first step is to find the values of x such that the denominator (x^2 + 3) is equal to zero.
Then we need to solve:
x^2 + 3 = 0
x^2 = -3
x = √(-3)
This is the square root of a negative number, then this is a complex number.
This means that there is no real number such that x^2 + 3 is equal to zero, then if x can only be a real number, we will never have the denominator equal to zero, so the domain will be the set of all real numbers.
D: x ∈ R.
b) we want to find two different numbers x such that:
r(x) = 1/4
Then we need to solve:
[tex]\frac{1}{4} = \frac{x + 1}{x^2 + 3}[/tex]
We can multiply both sides by (x^2 + 3)
[tex]\frac{1}{4}*(x^2 + 3) = \frac{x + 1}{x^2 + 3}*(x^2 + 3)[/tex]
[tex]\frac{x^2 + 3}{4} = x + 1[/tex]
Now we can multiply both sides by 4:
[tex]\frac{x^2 + 3}{4}*4 = (x + 1)*4[/tex]
[tex]x^2 + 3 = 4*x + 4[/tex]
Now we only need to solve the quadratic equation:
x^2 + 3 - 4*x - 4 = 0
x^2 - 4*x - 1 = 0
We can use the Bhaskara's formula to solve this, remember that for an equation like:
a*x^2 + b*x + c = 0
the solutions are:
[tex]x = \frac{-b +- \sqrt{b^2 - 4*a*c} }{2*a}[/tex]
here we have:
a = 1
b = -4
c = -1
Then in this case the solutions are:
[tex]x = \frac{-(-4) +- \sqrt{(-4)^2 - 4*1*(-1)} }{2*(1)} = \frac{4 +- 4.47}{2}[/tex]
x = (4 + 4.47)/2 = 4.235
x = (4 - 4.47)/2 = -0.235
Simplify the expression:
3y2 + 15 – 2y2
Answer: 16y
Step-by-step explanation: Done this before so easy obviously 16y
Answer:
=y^2 + 15
Step-by-step explanation:
Find the mean: 1, 4, 4, 6, 10
Answer: 5
Step-by-step explanation:
1. 1 + 4 + 4 + 6 + 10 = 25
2. 25/5 (divide by the amount of numbers)
Answer:
5
Step-by-step explanation:
First, add up all of the numbers.
1 + 4 + 4 + 6 + 10 = 25
Then count how many there are.
5
Lastly, divide the sum by the number of numbers.
25/5 = 5
This will give you your answer.
Hope this helped!
need a little help please
Answer:
[tex] \sqrt{1314} [/tex]
Step-by-step explanation:
a²+b²=c² so: 33²+15²=x²
1089+225=x²
1314=x²
take the square root of both sides
36.249=x or
[tex] \sqrt{1314 } [/tex]
=x
help help help help help help help helphelp help help helphelp help help helphelp help help help
Answer:
X = 36/17
y = -8/17
Step-by-step explanation:
Since they both equal y, you could use them equal to each other.
(5/2)x-4=(-1/3)x+2
Then solve for x by combining like terms. X should be 36/17. Plug in x to find y in one of the equations. I will use the top one. (5/3)(36/17)-4=y. That should simplify down to (60/17)-4=y. Y would finally equal -(8/17).
Answer:
What the other guy said. I think he is correct.
Step-by-step explanation:
Fred purchased a piece of artwork for 6200, and it is expected to increase in value by 5% per year. Write a function y to represent the value of the piece of artwork after v years.
Answer:
y = a(1 + r) ^v
y = 6200( 1 + 0.05)^v
y = 6200(1.05)^v
Step-by-step explanation:
Fred purchased a piece of artwork for 6200, and it is expected to increase in value by 5% per year. Write a function y to represent the value of the piece of artwork after v years.
The function we can used to represent the above question is given as Exponential Growth function.
Where the number of years = v
The value of the artwork = y
y = a(1 + r) ^v
Where
a = Initial value of the artwork = 6200
r = Growth rate = 5% = 0.05
v = number of years
Therefore, the function y to represent the value of the piece of artwork after v years is written as:
y = 6200( 1 + 0.05)^v
y = 6200(1.05)^v
please help me on this will give you brainliest
A company donated $4,250 dollars to a school. There are 50 classes in the school. If each class receives the same amount of money to plan a field trip, how much money does each class receive
*Please show you work :)
Answer:
Each class receive $85.
Step-by-step explanation:
So what you will be doing is dividing $4,250 and the 50 classes.
Hope this helps or is right at least :)
HELP I DON'T UNDERSTAND THIS AT ALL!!!
D__ is 7.5<x
C is x<10
Step-by-step explanation:
just do the inequality and graph
what is the solution for X in the equation -4 + 5x - 7 equals 10 + 3 x - 2x
choices:
A- x= 4/21
B- x= 13/4
C- x= 4/13
D- x= 21/4
Answer:
x=21/4Step-by-step explanation:
expressions are equivalent to -7+3(-4e-3)−7+3(−4e−3)
Answer:
-7 - 12e - 9
I’m not sure what your asking for but that’s the simplified version of that’s what your looking for. And from there you can get the answer by simplifying the one I gave you which would give you
-12e - 16 ;)
Step-by-step explanation:
One cell phone company charges a $76 sign-up fee and $40 per month. Another cell phone company charges $136 sign-up fee and $20 per month. Write and solve an equation to determine after how many months the cost is the same
Answer:
The cost would be same after 3 months.
Step-by-step explanation:
Given that:
Charges of first company;
Sign up fee = $76
Per month charges = $40
Let,
x be the number of months
y be the total cost.
y = 40x + 76 Eqn 1
Charges of second company;
Sign up fee = $136
Per month charges = $20
y = 20x + 136 Eqn 2
For same cost,
Eqn 1 = Eqn 2
40x + 76 = 20x + 136
40x-20x = 136 - 76
20x = 60
Dividing both sides by 20
[tex]\frac{20x}{20}=\frac{60}{20}\\x=3[/tex]
Hence,
The cost would be same after 3 months.
Use the side-splitter theorem to solve for x in the triangle below.
Answer:
Step-by-step explanation:nfnfnfnfn
What is the value of the expression
what is the slope intercept form of the equation of a line that passes through the coordinates (3,-2) and (5, -4) ?
Answer:
m=-1x+1
Step-by-step explanation:
uhh i lookedmup the answer
if you add 5 to me then divide by 9 you get 3 what number am I?
Answer:
22 the answer is 22
Step-by-step explanation:
3*9= 27
27-5=22
You have to work backwards
If you put it together you get
22 add 5 you get 27
27 divided by 9 equals 3
I hope this helps!!!!!
Answer:
you are 22
Step-by-step explanation:
i hope im right... if not, sorry ;w;
Help me please on this question. Thanks.
please help me lol.
KHAN ACADEMY! what is the constant of proportionality in the equation: y=2x?
constant of proportionality=??
Answer:
2
Step-by-step explanation:
Compare y = 2x to y = kx, where y = kx is a proportional relationship.
We see that the constant of proportionality, k, is 2.
PLSSS HELP IM ON A TIME LIMIT
Hey do you mind helping me on the Redbox and I could really use some help an explanation if you know it thank you very much you made my day:)!!
Answer:
every day, (name) loses $2.00
we can see this by looking at the table, as one more day passes, the number of dollars decrease by 2
Find the midpoint of the line segment whose endpoints are (-2, 5) and (6, -9).
(2, -2)
(1, -4)
(4, -4)
Answer:
The midpoint of the line segment whose endpoints are (-2, 5) and (6, -9) is: (2,-2)
Step-by-step explanation:
Given two points are:
(-2, 5) and (6, -9)
The mid-point is the point that divides a line segment in two equal parts.
Let M be the mid-point then
[tex]M(x,y) = (\frac{x_1+x_2}{2}, \frac{y_1+y_2}{2})[/tex]
Let
(x1,y1) = (-2, 5)
(x2,y2) = (6, -9)
Putting the values in the formula, we get
[tex]M(x,y) = (\frac{-2+6}{2}, \frac{5-9}{2})\\M(x,y) = (\frac{4}{2}, \frac{-4}{2})\\= (2,-2)[/tex]
Hence,
The midpoint of the line segment whose endpoints are (-2, 5) and (6, -9) is: (2,-2)
Given that 4 x : 3 = 11 : 7 Calculate the value of x .
Step-by-step explanation:
4x/3=11/7
4x=11×3/7?
4x=33/7
4x=4.7
x=4.7/4
x=1.175
please mark mean as brilliant brainliest
In a survey of 3,200 people who owned a certain type of car, 960 said they would buy that type of car again. What percent of the people surveyed were satisfied with the car?
HELP NOW!!
Answer: let
Total number of those who took part in the survey (T)=3200
Those who were satisfied (t)=960
Percentage of those who were satisfied (S)=(t/T)*100
S=(960/3200)*100
S=30%
Therefore only 30% were satisfied
Step-by-step explanation:
Thirty percent of the people surveyed were satisfied with the car.
What is the formula used to find the percentage?The formula used to calculate percentages is the ratio of value to total value multiplied by 100.
Let's denote T as the total number of people who owned a certain type of car and t as the number of people who were satisfied with the car.
Given that,
T =3200
t= 960
The percent of people satisfied with the car is obtained by using the below equation.
[tex](\frac{t}{T} ) * 100[/tex]
(960/3200)*100 = 30%
As a result, the percentage of people who are satisfied with the car is 30%.
To learn more about percentage, use the link below:
https://brainly.com/question/29306119
#SPJ2